Behavior Trees for video games. Case study: Development of a 3D Action-Adventure game - Κυριαζής, Άγγελος; Βέργου, Φιλίππα-Ελένη (Πανεπιστήμιο Πελοποννήσου, 2025)
This thesis explores the use of Behavior Trees in artificial intelligence development for games, through the case study of developing a 3D Action-Adventure game in Unreal Engine 5.4. The aim of the study is to analyze the fundamental principles and techniques involved in their integration, as well as to document the challenges and solutions encountered during development.
Δέντρα συμπεριφοράς σε ηλεκτρονικά παιχνίδια. Μελέτη περίπτωσης: Ανάπτυξη 3Δ Παιχνιδιού Δράσης – Περιπέτειας.
Μ.Δ.Ε. 81
Keywords: Artificial Intelligence; Robots-Programming; Mathematical models; Video games; Τεχνητή νοημοσύνη; Ρομπότ-Προγραμματισμός; Μαθηματικά μοντέλα; Βίντεο παιχνίδια; Behavior Trees; Non-Player Characters; Unreal Engine; Artificial intelligence; Game engines; Δέντρα συμπεριφοράς; Τεχνητή νοημοσύνη; Mηχανές παιχνιδιών